Moving Beyond Biopower: Hardt and Negri's Post-Foucauldian Speculative Philosophy of History - Fillion, Réal Robert (History and theory, 2005)
I argue in this paper that the attempt by Michael Hardt and Antonio Negri in Empire and Multitude to “theorize empire” should be read both against the backdrop of speculative philosophy of history and as a development of the conception of a “principle of intelligibility” as this is discussed in Michel Foucault's recently published courses at the Collège de France. I also argue that Foucault's work in these courses (and elsewhere) can be read as implicitly providing what I call “prolegomena to any future speculative philosophy of history.” I define the latter as concerned with the intelligibility of the historical process considered as a whole. I further suggest, through a brief discussion of the classical figures of Kant, Hegel, and Marx, that the basic features of speculative philosophy of history concern the articulation of both the telos and dynamics of history. My claim is that Hardt and Negri provide an account of the telos and dynamics of history that respects the strictures imposed on speculative philosophy of history by Foucault's work, and thus can be considered as providing a post-Foucauldian speculative philosophy of history. In doing so, they provide a challenge to other “theoretical” attempts to account for our changing world.